Economic evaluation in education : cost-effectiveness and benefit-cost analysis - Levin, Henry M.; McEwan, Patrick J.; Belfield, Clive; Bowden, A. Brooks; Shand, Robert (Los Angeles, CA : SAGE Publications, Inc, 2018)
The past decade has seen increased attention to cost-effectiveness and benefit-cost analysis in education as administrators are being asked to accomplish more with the same or even fewer resources, philanthropists are keen to calculate their ‶return on investment" in social programs, and the general public is increasingly scrutinizing how resources are allocated to schools and colleges. This text (titled Cost-Effectiveness Analysis in its previous editions) is the only full-length book to provide readers with the step-by-step methods they need to plan and implement a benefit-cost analysis in education. The authors examine a range of issues, including how to identify, measure, and distribute costs; how to measure effectiveness, utility, and benefits; and how to incorporate cost evaluations into the decision-making process. The updates to the Third Edition reflect the considerable methodological development in the evaluation literature, and the greater empiricism practiced by education researchers, to help readers learn to apply more advanced methods to their own analyses.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Education -- Economic aspects